Intergenerational communication and elderly well-being - Josmitha Maria Dsouza; Anirban Chakraborty; Neetha Kamath (Elsevier, 2023)
Background: Mental fitness and well-being are essential elements of human life. They help humans overcome hardships and fulfill their desires successfully. This study looked at the effects of interaction with children on well-being among the elderly. Methods: A quasi-experimental pretest-posttest control group design was employed, and the institutionalized elderly were selected using a purposive sampling method. They were then allocated equally into experimental and control groups. Children included in the study were selected based on a validated rating scale that measured their attitude towards the elderly. The WHO (five) well-being index was used to gather data. The elderly in the experimental group had an opportunity to interact with the children once a week for 12 weeks whereas the control group didn't have access to the children. Results: There was a significant difference (P <0.001) in the mean posttest scores of well-being among the elderly in the experimental group (81.76±11.56) when compared to the control group (37.02±14.13). Conclusion: The findings of this study suggest that the interaction with children promotes well-being among the elderly. Interaction of children with the elderly residing in the elderly homes can be included as a part of the curriculum in schools and it may contribute to the holistic development of children's attitude.